Feminist moments : reading feminist texts - Bruce, Susan; Smits, Katherine (2016)
The challenges presented by feminism to traditional understandings of representation, normative values, power relations and the political are not simply the product of late-20th century thinking. Feminist Moments, in examining some of the pivotal texts in the history of feminist thought, demonstrates that these challenges emerge from a long and varied history of feminist writing. The volume brings together texts from literary and analytical works written by women and men, and from inside and outside the Western tradition, including Mary Wortley Montagu, Anna Wheeler and William Thompson, Nazira Zeineddine, Betty Friedan, Andrea Dworkin and Luisa Valenzuela. The volume is unique in offering close readings of key passages from the selected texts, making it ideal for classroom use; its original essays, all authored by specialists, will also be of interest to more advanced scholars. In juxtaposing and analysing a wide range of texts which despite their significance are rarely discussed together, Feminist Moments provides a fascinating historical narrative of feminist thought which will be highly valuable to students and scholars of the history of political thought, political philosophy and gender and literary studies.